The leadership challenge how to keep getting extraordinary things done in organizations - Kouzes, James M. 1945-; Posner, Barry Z. (Jossey-Bass management series, 1995)
With an expanded research base of sixty thousand leaders and constituents, this new edition of The Leadership Challenge captures the continuing interest in leadership as a critical aspect of human organizations. It offers a broader scope for viewing leaders in every industry and all walks of life, including the education and nonprofit fields.